Körper und Textualitäten: Subjektivierungsformen und Praktiken des Widerstands gegen Gewalt gegen Frauen im heutigen Argentinien - Nespolo, Maria Jimena (2020)
The emergence of the body as a scenario of tensions and demands allows us to observe the emergence at international level of an unprecedented political agency. In Argentina, the massive demonstrations denouncing gender violence have not been able to curb the rising rate of femicides, nor have they made the Government asume responsibilities in the matter. On the other hand, the media and fictional treatment of these deaths, and the conservative outbreak of a certain sector of society, multiply the questions regarding the effectiveness of certain texts that in principle seem to be defined as denuncialists.